Distal pouch reconstruction with transverse jejunoplasty after experimental gastrectomy - Hackert, Thilo; Dovzhanskiy, Dmitriy I.; Heiser, Felix; Bergmann, Greta; Schneider, Lutz; Werner, Jens (Langenbeck's archives of surgery, 2012)
PurposeVarious reconstruction methods with or without reservoir formation after total gastrectomy have been established. Transverse intestinoplasty has benefits as a functional peristalsis modification in rectal resections. In this study, we evaluate a distal pouch combined with a transverse jejunoplasty compared to standard Roux-en-Y reconstruction.MethodsTotal gastrectomy was performed on 23 pigs randomly assigned to 3 reconstruction groups—group 1 (n = 7): esophagojejunostomy without a pouch, group 2 (n = 8): esophagojejunostomy with a distal pouch, and group 3 (n = 8): distal pouch with a transverse jejunoplasty. Seven days postoperatively, weight was measured, and X-ray examinations were conducted for 1 h after oral contrast medium application. Blood glucose levels after oral glucose intake and the volume of the pouch loop were evaluated.ResultsUpper jejunal passage was delayed and the mean volume of the jejunal loop increased by pouch formation compared to controls (p < 0.05). Body weight was the best for the pouch group with jejunoplasty (−1.9 ± 0.8% vs. pouch alone −3.3 ± 2.4% vs. no pouch −7.5 ± 2.1%, p < 0.05).ConclusionsThe distal jejunal pouch after total gastrectomy offers advantages with respect to bowel passage and postoperative nutrition status compared to standard Roux-en-Y reconstruction. The combination of a distal pouch and transverse jejunoplasty may provide additional functional benefits.
Published online: 15 July 2011
Gesehen am 18.10.2018